DEVELOPMENT, OPTIMIZATION AND ASSESSMENT OF NAPROXEN MICROSPONGES BY BOX-BEHNKEN DESIGN AS A TARGETTED AND CONTROLLED RELEASE DRUG DELIVERY - GUPTA, SONIA; GUPTA, JYOTI (International Journal of Applied Pharmaceutics, 2024)
Objective: Due to weak physical, chemical stability and poor bioavailability of Naproxen conventional dosage form; the purpose of this work is to improve formulation stability, additionally to accomplish highest possible concentration of the drug in the blood by preparing Naproxen loaded microsponges. Methods: Naproxen Microsponge (NM) was created utilising the quasi emulsion technique. In this process Ethyl Cellulose (EC) acts as a polymer, Poly Vinyl Alcohol (PVA) acts as the emulsifier, and Dichloromethane acts as the solvent. To investigate how changes in different formulation and processing parameters affect important product qualities, a Box Behnken Design (BBD) was used. Particle Size, Percentage Yield, and Entrapment Efficiency (%EE) were selected as response factors, whereas independent variables including EC quantity (X1), PVA concentration (X2), and Stirring Speed (X3) were selected as independent variables. Results: The microsponges underwent thorough analysis using Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction (XRD), and Particle Size analysis. The evaluation included studying the morphology, drug loading, and in vitro drug release. The compatibility studies showed no chemical interactions between the drug and the polymers used. It was observed that the ratio of drug to polymer had a significant impact on drug content, EE and particle size. The SEM results revealed that the microsponges were spherical with a porous surface and had a mean particle size of 15.15 µm. The in vitro drug release studies demonstrated that the optimized Naproxen Microsponge Formulation (NMF2) achieved over 80% extended drug release by the end of 8 h, following the Corsmeyer Peppas Model. Conclusion: The Naproxen loaded microspheres possessed a sustained release with improved bioavailability and better stability.